MBEROT: TRANSFORMASI SENI PERTUNJUKAN BANTENGAN TRADISIONAL KE MODERN - Yuriananta, Renda; Salsabrina, Aprilia Selva; Aisy, Indi Rihhadatul; Azizah, Putri Aulia; Kumalasari, Putri; Ramadhani, Rizka Auliya; Firdaus, Herdian Puspa (Kusa Lawa, 2026)
The transformation of traditional performing arts is inseparable from social dynamics, technological advancement, and changing public needs. One prominent example is the evolution of the Bantengan performing art in Greater Malang, East Java, from its traditional form into the contemporary performance known as Bantengan Mberot. This study aims to describe the transformation process of Bantengan, analyze the shifts in its cultural meanings and identity, and examine the negotiation between cultural preservation and modernization. This research employed a qualitative approach with a cultural ethnography design. The study was conducted in several areas of Greater Malang where Bantengan communities actively preserve and perform this tradition. Data were collected through participant observation, in-depth interviews with performers, community leaders, event organizers, documentation, and literature review. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing through the interpretation of symbolic meanings from an anthropological perspective. The findings reveal that the transformation of Bantengan extends beyond changes in visual appearance, musical accompaniment, and performance technology to encompass shifts in its social functions and cultural meanings. Originally rooted in ritual and spiritual practices, Bantengan has evolved into a public performance that integrates entertainment, cultural identity representation, and the creative economy. Cultural symbols are continuously reinterpreted through a process of hybridity between tradition and modernity without eliminating the fundamental values embedded in the tradition. This study concludes that Bantengan Mberot represents a form of cultural adaptation that demonstrates the resilience of traditional performing arts through innovation while reinforcing the cultural identity of the Greater Malang community amid contemporary social transformation.